EARLY OUTCOMES OF ARTERIOVENOUS FISTULA INTERVENTION AT FRIENDSHIP HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe clinical and lesional characteristics and evaluate early outcomes (after 1 month) of endovascular intervention for arteriovenous access stenosis in hemodialysis patients. Subjects and methods: A descriptive, retrospective and prospective study on 47 end-stage renal disease patients on hemodialysis with significant access stenosis (> 50%) who underwent endovascular intervention at Friendship Hospital from 3/2023 to 12/2024.Results: The mean age of the patients was 71.9 ± 10.9 years, with 87.2% males. Hypertension (76.6%) and diabetes (53.2%) were common comorbidities. Radiocephalic arteriovenous fistula accounted for 76.6%. The most common stenosis location was the juxta-anastomotic area (51.1%), with a mean stenosis degree of 81.7 ± 10.3%, and lesion length of 42 ± 14 mm. Mean access flow before intervention was 350.7 ± 220.3 ml/min. Technical and clinical success rates were 100%. Post-intervention access flow improved significantly (654.7 ± 320.6 ml/min, p < 0.001). Minor complications included access site bleeding (6.4%) and venous spasm (8.5%). The 1-month restenosis rate was 4.3%. Conclusion: Endovascular intervention is a safe and highly effective method for treating arteriovenous access stenosis, especially in elderly patients, helping to restore and maintain hemodialysis functionality.
Keywords: Arteriovenous fistula stenosis, endovascular intervention, balloon angioplasty, hemodialysis.